KESUCIAN DIRI PINANDITA SEBAGAI MANGGALA DALAM PELAKSANAAN UPACARA YAJÑA - Widana, I Nyoman Murba (Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, 2019)
This research was conducted to study the self-purity of pinandita as a Hindu saint who has the authority to lead the yajña ceremony. This study was designed in a type of interpretive qualitative research. The design of this study is more of a literature study because to study the aspects of pinandita's personal purity taken from a number of scriptural texts which are then interpreted to understand the meaning implied in the text. The results of this study indicate that the process of cleansing a person to become a pinandita begins with doing pawintenan. The initiation process aims to purify a person to become a saint through the process of learning. After becoming pinandita there are a number of taboos that must be avoided in order to always maintain purity. In addition to taboos that must be avoided, a pinandita must also carry out self-purification activities, both physically and spiritually. Self-purification is very important for a pinandita because the authority attached to him in leading the implementation of Hindu ceremonies is in accordance with the yajña category held by Hindus